Price earning ratio, ukuran dan nilai perusahaan pada perusahaan manufaktur di Indonesia - Wiratno, Dwi Haryono; Yustrianthe, Rahmawati Hanny (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of price earning ratio and size on value of the company in manufacturing companies listed on the IDX for the 2015-2019 period. This research is a associative research. The population in this study were 177 companies listed on the IDX. The sample selection used a purposive sampling techinique and the research sample was obtained from 63 issuers financial reports. The data in this study are secondary data obtained from the Indonesia Stock Exchange (BEI) and the official website of the company concerned. The data analysis used was descriptive analysis followed by the requirements test including normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The statistical method used to analyze the data uses multiple linear regression analysis. The result showed that price earning ratio has a positive and significant on value of the company. Meanwhile size do no have a positive and significant on value of the company listed on the IDX for the 2015-2019 period.